The Influence of TikTok Shop and Brand Awareness on the Purchase Intentions of Mybellin Blush-On - Ida Ilham Ramadhan; Suharyanto (LP2M IAIN Palopo, 2026)
This study aims to determine and analyze the influence of TikTok Shop and Brand Awareness on the Purchase Intention of Maybelline blush-on products among students of the Faculty of Economics and Business at PGRI Adi Buana University Surabaya. The rapid development of social media, especially TikTok, has changed marketing strategies and consumer behavior through the concept of social commerce which integrates entertainment, interaction, and transactions within a single digital platform. This research used a quantitative approach with a survey method by distributing questionnaires to 90 female students of the Faculty of Economics and Business at PGRI Adi Buana University Surabaya who actively use TikTok and have seen or interacted with Maybelline blush-on products through TikTok Shop. The sampling technique used was non-probability sampling with an accidental sampling method. Data analysis was conducted using multiple linear regression analysis with SPSS, including validity tests, reliability tests, classical assumption tests, t-tests, and F-tests. The results of this study indicate that TikTok Shop has a positive and significant effect on purchase intention, Brand Awareness has a positive and significant effect on purchase intention, and TikTok Shop and Brand Awareness simultaneously have a significant effect on purchase intention of Maybelline blush-on products among students of the Faculty of Economics and Business at PGRI Adi Buana University Surabaya